Congo Red-Agar Plating Medium for Detecting Pigmentation in Pasteurella pestis - Surgalla, Michael J. (1969)
Ability to detect pigmented and nonpigmented Pasteurella pestis is essential in plague research, and is currently dependent on use of the synthetic hemin-agar of Jackson and Burrows. We have devised a new differential medium for this purpose, containing Congo red dye and common, commercially available laboratory media. The ease and simplicity of preparation make the Congo red-agar a practical routine laboratory tool in plague research. These findings, possibly indicating a common binding site for hematin and Congo red, should be useful in efforts to determine the chemical nature of a bacterial component associated with high virulence in P. pestis.